Ethiopian coffee: Production systems, geographical origin traceability, and European Union deforestation regulation directive compliance - Markos Makiso Urugo; Mohammed Worku; Yetenayet B. Tola; Habtamu Fekadu Gemede (Journal of Agriculture and Food Research, 2025)
Arabica coffee (Coffea arabica L.) is one of the two most widely cultivated coffee species globally, with Ethiopia being the fifth-largest producer. The European Union Deforestation Regulation (EUDR) (EU 2023/1115) mandates that companies importing coffee and other commodities into EU member states demonstrate that their products do not contribute to deforestation or forest degradation. This article examines Ethiopian coffee production systems, their geographical origin traceability, and their potential compliance with the EUDR. The Ethiopian coffee-based agroforestry system, which integrates coffee plants with native shade trees, supports sustainable land use and biodiversity conservation while providing significant ecological, socio-economic, and cultural benefits. However, the system's complexity poses challenges to the EUDR's definitions of deforestation, as it fosters biodiversity and ecological balance. The stringent requirements of the EUDR may disproportionately affect smallholder farmers who rely on this sustainable agroforestry practice. Furthermore, while traceability is essential for compliance, the associated costs and administrative burdens could threaten farmers' livelihoods and have negative impacts on Ethiopia's economy, which is heavily reliant on coffee exports. Future traceability developments include advancements in analytical techniques such as metabolomics and stable isotope ratio fingerprinting, as well as the strengthening of regulatory frameworks, enhanced stakeholder collaboration, and increased investment in traceability systems. Implementing supportive policies will be vital to ensuring Ethiopian coffee's compliance with international standards while maintaining sustainability. By promoting robust traceability, certification, and policy support, Ethiopian coffee agroforestry systems can succeed on a global scale, fostering sustainable and deforestation-free supply chains.